Microbiological profile and cytological alterations associated with cervico-vaginal samples collected at a philanthropic institution in the state of Sergipe (Research, Society and Development, 2021)
Cervical cancer is a public health problem, being the third most common type of cancer in women in Brazil, and it can be diagnosed through cytopathological examination. The objective of the work is to analyze the microbiological profile and cytological changes associated with cervicovaginal collected in a philanthropic institution, in the state of Sergipe. This is a retrospective, descriptive and cross-sectional research, in which the results of the medical records of women who underwent cytopathological examination between the months of July and October 2017 were carried out. During the study period, 500 cytopathological examinations were performed. 96% (480/500) of the Subsidiaries were considered satisfactory and 4% (20/500) unsatisfactory. When analyzing the microbiological profile, it is noted: Mixed Microbiota in 31.2% (156/500) of cases, Cocos in 29.45 (147/500), Lactobacilli without cytolysis in 16% (80/500), Lactobacilli with cytolysis in 9.2% (46/500), Supracytoplasmic bacilli in 7.4% (37/500), Cocobacilli in 1.6% (8/500), Candida spp. in 2.4% (12/500), Trichomonas vaginalis in 0.8% (4/500) and Absence of microorganisms in 1.6%. The cytological findings were represented as follows: Inflammation in 73.6% (368/500) of cases, Double Alteration, that is, Atrophy with Inflammation and Immature Squamous Metaplasia and/or Inflammation with Immature Squamous Metaplasia 13.4% (64/500) of the cases, Atrophy with Inflammation in 9.4% (47/500), within the limits of Normality in 3.4% (17/500) and Immature Squamous Metaplasia in 1% (5/500) of the results. Therefore, the number of microorganisms found in the results were high. Regarding cytological changes, it was observed that inflammation was present in most cases.